Aesthetic experiences in teaching: cinema as a formative device - Vasconcellos, Vanessa Alves de Silveira de (2014)
The formation power and contributions to the teaching aesthetic experience that cinema arouses in academic spaces and timing is evident, both in the early or continued education of teachers. We believe that it would be important to think on the teaching formation, about educating the views, the sensitivity, and cinema, regarding such matters, may provoke formation, and more specifically, may implicate people in aesthetic and ethical experiences. Thus, we present an experience developed with teachers from Santa Maria, RS, originated from the research developed by the Study and Research Group GEPEIS, with the Project: “Within times of formation ”“ cinema, life and caring for oneself: Autobiographical and collective exercises in the teaching activity”.